Vaccine Effectiveness Against Acute Respiratory Illness Hospitalizations for Influenza-Associated Pneumonia During the 2015–2016 to 2017–2018 Seasons: US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN) - Ghamande, Shekhar; Shaver, Courtney; Murthy, Kempapura; Raiyani, Chandni; White, Heath D; Lat, Tasnim; Arroliga, Alejandro C; Wyatt, Dayna; Talbot, H Keipp; Martin, Emily T; Monto, Arnold S; Zimmerman, Richard K; et al. (Clinical infectious diseases, 2022)
Abstract Background Evidence for vaccine effectiveness (VE) against influenza-associated pneumonia has varied by season, location, and strain. We estimate VE against hospitalization for radiographically identified influenza-associated pneumonia during 2015–2016 to 2017–2018 seasons in the US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN). Methods Among adults aged ≥18 years admitted to 10 US hospitals for acute respiratory illness (ARI), clinician-investigators used keywords from reports of chest imaging performed during 3 days around hospital admission to assign a diagnosis of “definite/probable pneumonia.” We used a test-negative design to estimate VE against hospitalization for radiographically identified laboratory-confirmed influenza-associated pneumonia, comparing reverse transcriptase–polymerase chain reaction–confirmed influenza cases with test-negative subjects. Influenza vaccination status was documented in immunization records or self-reported, including date and location. Multivariable logistic regression models were used to adjust for age, site, season, calendar-time, and other factors. Results Of 4843 adults hospitalized with ARI included in the primary analysis, 266 (5.5%) had “definite/probable pneumonia” and confirmed influenza. Adjusted VE against hospitalization for any radiographically confirmed influenza-associated pneumonia was 38% (95% confidence interval [CI], 17–53%); by type/subtype, it was 74% (95% CI, 52–87%) influenza A (H1N1)pdm09, 25% (95% CI, −15% to 50%) A (H3N2), and 23% (95% CI, −32% to 54%) influenza B. Adjusted VE against intensive care for any influenza was 57% (95% CI, 19–77%). Conclusions Influenza vaccination was modestly effective among adults in preventing hospitalizations and the need for intensive care associated with influenza pneumonia. VE was significantly higher against A (H1N1)pdm09 and was low against A (H3N2) and B. Vaccine effectiveness against adult acute respiratory illness hospitalization for radiographically identified laboratory confirmed influenza-associated pneumonia estimated using a test-negative design was 38% (95% confidence interval: 17-53%) during 2015-2016 to 2017-2018 in the US Hospitalized Adult Influenza Vaccine Effectiveness Network (HAIVEN).